HEREDITY OF BAND PATTERN IN CLOWN FISH, Amphiprion percula - Sari B.M. Sembiring; K.M. Setiawati; J.H. Hutapea; W. Subamia (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2013)
One of marine ornamental fishes which was succeeded on its breeding, from eggs production to larval and juvenile rearing at Institute for Mariculture Research and Development, Gondol was Clown fish, Amphiprion percula. In local name, the fish also known as Biak Clown fish. In culture development, the fish frequently faced the problem on color pattern which was not meet with export demand. The fish should be bright orange and thin black stripe pattern. In this experiment, analysis was conducted to understand the juvenile color variation produced from 3 pairs broodstock. Larvae and juvenile were reared in the indoor hatchery for 2-3 months,then reared at outdoor tanks for other 3-4 months. Amplification of broodstock and juvenile genoms using specific primer for pigment sequens. Parameters observed on juvenile were classified into three color pattern classes i.e., class I (thick black stripe and disperse), class II(thick black stripe), and class III (thin black stripe). Numbers of juvenile analyzed from its pair broodstock and each class were 2-3 fishes. Color perform similarity coefficient was analyzed molecularly using sequencing. Sequencing process followed: DNA isolation, amplification using gen Tyr primer, purification PCR product and finally DNA sequencing. Sequencing analyses of PCR product, after alignment showed that similarity coefficient of color pattern of class I, II, and III between broodstock and juvenile was only 50 %, and phenotipically, color pattern appeared on juvenile were different than its broodstock. The changes of color perform on Clown fish also affected by interaction between genotype and environment and feed pigment concentration.Keywords: heredity, color pattern, Tyr gene, clown fish, A. percula